Clinically Oriented Anatomy Jilid 1, 2, 3 : thorax, abdomen, perineum and pelvis - MOORE, Keith L. (WILLIAMS & WILKINS, 1985)
Clinically Oriented Anatomy Jilid 1, 2, 3 : thorax, abdomen, perineum and pelvis